A simple, effective approach for rapid development of high-throughput and reliable LC–MS/MS bioanalytical assays. (September 2016) - Yuan, Long; Aubry, Anne-Françoise; Ji, Qin C
Background: Rapidly developing LC–MS/MS assays with high-throughput and quality are challenging yet desired.Methodology & results: A simple method development approach was reported and demonstrated with the quantitative bioanalysis of BMS-984478, a hepatitis C virus nonstructural protein 5A inhibitor. An accurate, precise and robust LC–MS/MS method for the quantitation of BMS-984478 in rat and monkey plasma was developed and validated. Incurred sample reanalysis evaluation passed with 100% of samples meeting the acceptance criteria. The validated assay was successfully applied in toxicology studies without any failed runs.Conclusion: The approach was successfully applied to the bioanalysis of BMS-984478 in toxicology and clinical studies. This approach was shown to be effective and reliable in speeding the development of high-throughput and reliable LC–MS/MS assays.